Mediação cultural e incentivo à leitura em escola pública: a democratização do conhecimento para alunos do 7º ano do Colégio Estadual Olavo Bilac - Vieira, Camila Conceição Barreto (2020)
The present study has the general objective of developing a guide for cultural mediation and encouraging critical reading for young people at Colégio Estadual Olavo Bilac. It is an applied research, with a qualitative approach and the universe of research is the students of the school. Data collection was based on observations, data analysis and questionnaires, which served as a basis for the design of the intended action. The intervention is based on the use of multimedia resources and texts with contemporary themes that aim to contextualize the project's participants about the theme worked on, broaden the discussion on these subjects, showing a critical view of the facts, enabling young people to acquire autonomy in the process teaching-learning. For this, the activity was divided into three stages, which are contextualization, proposition and sharing, in which project participants can appropriate the content worked on and produce knowledge through the debates provoked in the classroom. Concurrently with the work done, Portuguese and history teachers will address the same issue in the classroom, in order to show the various points of the same subject. The theme initially chosen is that of censorship, which was selected through the diagnosis carried out, in which it was verified the common interest of students with youtuber Felipe Neto, who at the time of the research proposal was involved with the controversy of the of the then mayor's censorship Marcelo Crivella at the “Bienal do Livro.” The results were configured for the formatting of a guide that has the function of orientation as a mediation model for application in public schools in the future.